Preliminary study of asymmetric ultrafiltration (UF) membrane: the effect of coagulation bath temperature (CBT) and forced convection resident time (FCRT) on the permeability and morphology of UF polysulfone membrane / Asmadi, A. …[et al.] - A, Asmadi; A. H, Nurbaiti; N, Ali; A. R., Hassan; R. M., Yunus (2008)
Previous studies have shown that the forced convection resident time (FCRT) and coagulation bath temperature (CBT) have significantly influenced the permeability characteristics of the membrane, thus affected the membrane performances. In this study, the UF Polysulfone membranes were prepared by varying of two rheological factors, which applied with different coagulation bath temperature at 10°C, 30°C, and 50°C and different forced convection resident time which was at 10 s, 15 s, and 20 s. The objective of this study is to investigate the effect of those rheological factors to pure water permeability (flux) and morphology of UF Polysulfone membranes. The membranes were fabricated using a ternary dope formulation of 14.4% Polysulfone (PSF), 81.6% N-methyl-2 pyrrolidone (NMP), and 4% water by a dry/wet phase inversion process by using an electrically controlled flat sheet membrane casting machine. The membranes were characterized by the permeation test of pure water flux and its morphology via scannimg electron microscope (SEM). The permeability and morphology of the UF Polysulfone membranes which were prepared via phase inversion technique are strongly influenced by varying forced convection residence time and coagulation bath temperature.